Impact of Religiosity On Travel Intentions and Behaviors - Datta, Gargi (My University, 2025)
Travel is a unique activity to seek solace, break monotony, and at times to find purpose. It is a journey that takes us not only across the world but also into the depths of our own souls. This research delves into the complex interplay between religiosity, personality, and the quest for meaning in life, examining their impact on travel intentions and behaviors. It employs a two-phase approach: an initial comparative study of travellers to religious (Prayagraj) versus non-religious (Agra) sites revealing distinct psychological profiles, followed by a comprehensive analysis of 610 working professionals to assess how these factors influence travel decisions. The study introduces two new scales for measuring travel intentions and behaviors, addressing a gap in extant literature. Key findings indicate that different aspects of religiosity, viz., intellectual, ideological, private practice, and religious experience, each uniquely shape travel preferences, with personality dimensions like negative emotionality and conscientiousness, and the search for or presence of meaning in life, serving as significant moderators. Intellectual religiosity increases intentions to visit religious sites, while ideological religiosity expands interest in new and beautiful destinations. Moreover, seeking life's meaning enhances the influence of ideological religiosity on the desire to visit religious as well as new destinations. In contrast, having a defined sense of life's purpose influences travel intentions driven by religious and intellectual motivations. By exploring the roles of religiosity, personality, and meaning in life, this research yielded important insights for both academia and the travel industry, emphasizing personalized tourism based on individual predilections, laying a foundation for future research and practical applications.
Keywords: managemnet; travel; marketing; psychology; religiosity